MENYINGKAP KEMATIAN DALAM GAGASAN SEIN-ZUM-TODE ADA-MENUJU-KEMATIAN MENURUT MARTIN HEIDEGGER - Eric Yohanis Tatap (Aggiornamento, 2022)
The talk about death in the context of pandemic is an interesting issue to study. Death is not merely reduced as a result of the pandemic, but needs to be realized as a basic limited and temporary human trait. The purpose of this study is to tame the perception of death in the struggle of human life in the midst of tense situations. The methodology used in the study is a qualitative method with phenomenologically critical data exposure. Literature review are used to collect data. Data analysis using the Heideggerian ontology approach. The findings in this study suggest that humans will in fact experience or face the death. Sooner or later humans will experience it. To tame the fears of human death is to anticipate and behave towards that reality. The attitude that needs to be collected is to look at death in a rationality and be critical of it.